A new facile and efficient synthesis of 2-((5-aryl-1,3,4-oxadiazol-2-yl) methoxy)-3-methyl quinoxaline and 3-methylquinoxalin-2-yl-2-(5-aryl-2H-tetrazol-2-yl)acetate derivatives - Kethireddy, Shashikala; Kotakommula, Hemalatha; Eppakayala, Laxminarayana; Mariganti, Thirumala Chary (European Journal of Chemistry, 2017)
Newly synthesized compounds containing quinoxaline ring fused with tetrazoles and oxadiazoles show array of pharmacological activities, especially, anti-inflammatory, analgesic and anticonvulsant activities. The ability to serve as surrogates or bioisosteres for carboxylic acids, esters and carboxamides made them important moieties in drug designing. Considering the importance of quinoxalines, tetrazoles and 1,3,4-oxadiazoles to both medicinal and heterocyclic chemistry, the following 2-((5-aryl-1,3,4-oxadiazol-2-yl)methoxy)-3-methyl quinoxaline and 3-methylquinoxalin-2-yl-2-(5-aryl-2H-tetrazol-2-yl)acetate derivatives are synthesized. The structures of the synthesized compounds were confirmed by 1H NMR, 13C NMR and Mass spectral data. All the synthesized derivatives were tested in vitro for their antibacterial activity.